ASSESSING THE STATE OF COMPETITIVE ENVIRONMENT IN UKRAINE BASED ON INTERNATIONAL RANKINGS - Ocheretna, Mariya (Journal of European Economy, 2017)
The article provides an assessment of the Ukraine’s competitive environment on the basis of international rankings, identifies its strengths and weaknesses highlighting those which should become the object of special attention by the regulators. Author performs the survey of national state policy on improving the competitive environment and provides with suggestions for its improvement.